Participatory identification of reproductive problems among dairy animals and constraints faced by farmers in Haryana - MEENA, M S; MALIK, B S (The Indian Journal of Animal Sciences, 2011)
The study investigates the prominent reproductive problems among dairy animals and associated constraints in its medication. Study was undertaken in 12 villages of Karnal district (Haryana) in participatory mode. Responses were obtained from 300 dairy farmers who had at least one milch cattle. Results revealed that repeat breeding followed by anoestrus was observed as prominent reproductive problems. Mostly farmers had faced medium level of reproductive problems (74.33%). The major identified constraints were lack of facility of doctors during night, high incidence of repeat breeding, and lack of good quality bulls at village level. Mostly respondents faced medium level of constraints (61.67%) in medication of these reproductive problems. There is need of an efficient extension setup, well equipped with know-how, and with solid infrastructural back up which can cater the needs of dairy farmers. Imparting quality practical training and periodical assessment of performance of lay inseminators will improve their skill and knowledge level. Extension machinery has to be an ideal bridge between research/development institutions and dairy farmers for their catalytic effect.Â